ASSESSMENT AND EVALUATION: NEW APPROACHES TO FORMATIVE AND SUMMATIVE ASSESSMENTS THAT ENHANCE LEARNING OUTCOMES - Freya Wilson (Bright Mind Publishing, 2025)
In recent years, educational research has increasingly focused on enhancing learning outcomes through innovative assessment practices. Traditional methods of assessment, especially summative assessments, have been criticized for their focus on memorization and their limited ability to gauge students' deeper understanding and skills. This paper examines emerging approaches in both formative and summative assessments that aim to improve student learning outcomes. It explores the shift towards assessment methods that prioritize active learning, critical thinking, and personalized feedback, in contrast to traditional, high-stakes exams. Key strategies, such as performance-based assessments, peer assessments, and digital portfolios, are discussed in the context of their role in fostering a more holistic approach to education. This study also addresses challenges to the implementation of these methods and suggests ways forward for educators and policymakers.
Keywords: Formative Assessment, Summative Assessment, Learning Outcomes, Innovative Assessment, Performance-Based Assessment, Peer Assessment, Digital Portfolios.